Self-Efficacy in Mathematics Learning and Efforts to Improve It - Aswin Aswin; Tatang Herman (Program Studi Tadris Matematika IAIN Salatiga, 2022)
This research was conducted to determine the effect of self-efficacy on mathematics learning achievement of students in class XI IPA SMA in Riau and efforts to improve it. This research is a descriptive quantitative research combined with correlational research, with a research sample of 30 students from class XI IPA SMA in Riau who were selected using random sampling technique. Data collection techniques are filling out questionnaires, tests, and interviews. The data collection instruments are: (1) self-efficacy questionnaire, (2) mathematics learning achievement test, and (3) interview to increase self-efficacy. Data were analyzed by descriptive statistics and inferential statistics, namely simple regression analysis. The results showed that: (1) students' self-efficacy was in the medium category, (2) students' mathematics learning achievement was in the medium category, (3) self-efficacy had a positive and significant effect on students' mathematics learning achievement, (4) efforts that could What is done in increasing student self-efficacy is (4.1) giving students opportunities to answer existing problems, (4.2) giving awards, (4.3) using models that make students play an active role in learning (4.4) providing positive reinforcements to students, (4.5) providing equal opportunities to all students, (4.6) using group learning and (4.7) using peer tutors.